2006
DOI: 10.1007/s00705-006-0814-z
|View full text |Cite
|
Sign up to set email alerts
|

Subtype IV of the BK polyomavirus is prevalent in East Asia

Abstract: BK polyomavirus (BKV) is ubiquitous in human populations, infecting children asymptomatically and then persisting in the kidney. Using either serological or genotyping methods, BKV isolates have been classified into four subtypes (I-IV), with subtype I mainly detected in all countries studied so far. To elucidate the subtype of BKV prevalent in East Asia, we examined BKV-positive urine samples collected from immunocompetent elderly patients in Mongolia, Northeast China, Northwest China, Southeast China, Southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Since it has been shown that JCV has coevolved with human populations (24), we recently started a series of studies to elucidate relationships between BKV lineages and human populations (3,9,25). In some of these studies, we used BKV DNA from urine samples collected from nonimmunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown that JCV has coevolved with human populations (24), we recently started a series of studies to elucidate relationships between BKV lineages and human populations (3,9,25). In some of these studies, we used BKV DNA from urine samples collected from nonimmunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Two American populations in North-east USA and southern California, two European populations in Finland and Ireland/England, and two Asian populations in Japan and China were examined in this study. The population in North-east USA is described in this study, whilst the other populations have been described previously Chen et al, 2006;Suzuki et al, 2002;Takasaka et al, 2004). The population in North-east USA consisted of three groups with different clinical status: healthy volunteers, non-immunosuppressed patients and immunosuppressed renal transplant (RT) patients (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Even taking the 95% highest posterior density intervals into account, the time scale provided using this calibration point clearly dates the evolution and divergence of BKVs (2.2 Myr ago) far prior to the appearance and radiation of modern humans (0.195 Myr ago;McDougall et al, 2005), and does not offer an explanation for the observed relationships between BKV lineages and human populations (Zheng et al, 2007). There are several reports on the prevalence of BKV subtypes and subgroups (Agostini et al, 1995;Baksh et al, 2001;Chen et al, 2006;Di Taranto et al, 1997;Ikegaya et al, 2006;Jin et al, 1993aJin et al, , 1995Krumbholz et al, 2006;Takasaka et al, 2004), and the data indicate a complex regional distribution pattern. An even earlier timescale for BKV evolution was obtained by Nishimoto et al (2006).…”
Section: Evolution Of Bkv Subtypesmentioning
confidence: 99%
“…Furthermore, there is evidence that BKV infection is a prominent risk factor for bladder carcinoma in immunocompetent individuals (Weinreb et al, 2006). The regional distribution of the BKV subtypes has been established in several studies (Agostini et al, 1995; Baksh et al, 2001; Chen et al, 2006;Di Taranto et al, 1997;Ikegaya et al, 2006;Jin et al, 1993aJin et al, , 1995Krumbholz et al, 2006;Takasaka et al, 2004). Subtype I is most prevalent, followed by subtype IV, with subtypes II and III occurring less frequently.…”
Section: Introductionmentioning
confidence: 99%